Evaluasi Program Tahfizh Qur'an di Sekolah Menengah Atas Islam Terpadu Kota Palopo - Suriadi, Syahril; Pirol, Abdul; Salmilah, Salmilah (Universitas Muhammadiyah Magelang, 2026)
This study evaluates the effectiveness of Quran tahfizh programs in three integrated Islamic high schools (SMAIT) in Palopo City (Insan Madani, Ibnu Sina, Wahdah Islamiyah) using the CIPP model, addressing challenges like time constraints, informal curricula, and varying student abilities in regular classes. The objective is to comprehensively and comparatively assess context, input, process, and product aspects. A qualitative evaluative-comparative approach was employed, with the population comprising program stakeholders and purposive samples including principals, tahfizh teachers, and students. Instruments of interviews, observations, and documentation were analyzed via Miles and Huberman's interactive model with triangulation. Findings reveal very good context and process, adequate input and product; SMAIT Wahdah Islamiyah excels across aspects. It is concluded that the program is overall effective but requires curriculum and facility improvements.